An enhanced architecture for serial fusion based multi-biometric verification system - Hossain, Shafaeat; Chen, Jundong; Rahman, Khandaker Abir (Institute of Electrical and Electronics Engineers Inc., 2018)
The traditional architecture of serial fusion based multi-biometric verification systems places an average performing or the worst performing individual verifier in the final stage. Because the final stage gives the verification decision using a single threshold and takes on the most confusing samples which are rejected by all previous stages, an average or the worst performing individual verifier may incur high verification errors in the final stage, which may negatively impact the performance of the whole system. Unfortunately, it is not possible to place a strong individual verifier in the final stage of a traditional architecture because if we place a strong individual verifier in the final stage, we will have to place a weak individual verifier in an earlier stage. Studies show that placing a weak individual verifier in an earlier stage worsens the performance of the whole system by giving more wrong decision earlier. Hence, the challenge is-how can we place the best performing individual verifier in the first stage and at the same time not place an average or the worst performing individual verifier in the final stage? In this paper, we address this challenge. We have come up with a very simple but effective solution. We have proposed a modification to the traditional architecture of serial fusion based multi-biometric verification systems. With rigorous experiments on the NIST multi-modal dataset and using three serial fusion based multi-biometric verification schemes, we demonstrated that our proposed architecture significantly improves the performance of serial fusion based multi-biometric verification systems. © 2018 IEEE.
Keywords: Architecture; Biometrics; Effective solution; Multi biometrics; Multi-modal dataset; Network architecture; Proposed architectures; Serial fusion; Traditional architecture; dept.csc

Movement pattern based authentication for smart mobile devices - Rahman, Khandaker Abir; Tubbs, Dustyn J.; Hossain, Md Shafaeat (2018 17th IEEE International Conference on Machine Learning and Applications (ICMLA), 2018)
We outline a novel method of user authentication for smart mobile devices, such as smartphones or tablets and propose movement pattern based authentication as an alternate to current methods that relies on a pin or drawn-pattern. While the current methods are vulnerable against common attacks (e.g., smudge attacks, shoulder surfing), our method, in contrast, is more resilient against the attacks of these kinds because it utilizes sensory data given off by the device during a preset movement for authentication. In our experiment, we recorded the values given off by four physical observational sensors: (1) accelerometer, (2) linear accelerometer, (3) gyroscope and (4) tilt sensor, which each had three axes, over a set of movements. We experimented with 10 arbitrary movement-patterns and gathered 12 samples of each (net 120 samples) to test with. We developed our own method of authentication, through which we performed 35,650 authentication attempts and found a 20.36% Equal Error Rate.
Keywords: Accelerometers; Authentication; Equal error rate; Gyroscopes; Linear accelerometers; Machine learning; Mobile computing; Mobile device; Movement pattern; Screen unlock; Sensory data; Shoulder surfing; Smart phones; Three axes; Tilt sensor; Training; User authentication; accelerometers; authentication; authorisation; dept.csc; gyroscope; gyroscopes; linear accelerometer; message authentication; mobile computing; mobile device; movement pattern; movement pattern based authentication; movement pattern, authentication, screen unlock, mobile device; physical observational sensors; preset movement; screen unlock; smart mobile devices; smart phones; smudge attacks; tilt sensor; user authentication

An empirical study on verifier order selection in serial fusion based multi-biometric verification system - Hossain, Md Shafaeat; Rahman, Khandaker Abir (Springer International Publishing, 2017)
Selecting the order of verifier in a serial fusion based multi-biometric system is a crucial parameter to fix because of its high impact on verification errors. A wrong choice of verifier order might lead to tremendous user inconvenience by denying a large number of genuine users and might cause severe security breach by accepting impostors frequently. Unfortunately, this design issue has been poorly investigated in multi-biometric literature. In this paper, we address this design issue by performing experiments using three different serial fusion based multi-biometric verification schemes, in particular (1) symmetric scheme, (2) SPRT-based scheme, and (3) Marcialis et al.’s scheme. We experimented on publicly available NIST-BSSR1 multi-modal database. We tested 24 orders—all possible orders originated from four individual verifiers—on a four-stage biometric verification system. Our experimental results show that the verifier order “best-to-worst”, where the best performing individual verifier is placed in the first stage, the next best performing individual verifier is placed in the second stage, and so on, is the top performing order for all three serial fusion schemes mentioned above.
Keywords: Biometric verification; Biometrics; Crucial parameters; Intelligent systems; Multi biometrics; Multi-biometric verification; Multibiometric systems; Multimodal database; Order selection; Security breaches; Serial fusion; Verifier order selection; dept.csc